Prácticas ancestrales empleadas por los médicos tradicionales (The Wala ́s) del resguardo indígena Nasa de Corinto, Cauca frente al aislamiento por la COVID-19 - Hernández Meza, Ervin Freineth; Quiguapumbo Valencia, Maydely; Gasca Sánchez, Yulieth Alexandra (Universidad Antonio Nariño, 2022)
This research describes and reports the importance of the ancestral practices that the indigenous community implemented during the isolation by the SARS COV-2 virus, due to the increasing increase of symptomatic and asymptomatic positive cases of COVID-19 that affected their ancestral territory, in the municipality of Corinto (Colombia). The objective was to know and describe the ancestral practices of isolation against COVID19 carried out by the traditional doctors (the Wala's) and authorities of the indigenous community during the isolation. The research was conducted under a descriptive qualitative methodology, using a semi-structured interview, with 6 guiding questions, to two traditional ancestral doctors and two authorities knowledgeable about the ancestral practices for the isolation of the community against COVID-19. The indigenous authority in the ancestral practices, in the first instance, is a representative belonging to the community with a mandate for 4 years, the authority is characterized by acquiring a responsibility and exercising leadership to support the community and provide care in spaces such as: working together with Mother Nature to heal through practices and knowledge in order to heal and protect the Nasa territory.